Gender and online politics: digital media as friend and foe in times of change - Boulianne, Shelley; Koc-Michalska, Karolina; Vedel, Thierry (My University, 2019)
This volume highlights gender issues related to using digital media for online politics. The submissions offer a balanced perspective about the role of digital media; this tool can be used for social change or to limit social change. The submissions use qualitative and quantitative analyses of digital trace data and survey data to present a rich perspective on gender and online politics. The collection offers a cross-national perspective including research on China, Germany, Norway, Spain, the United States, and the United Kingdom.
Keywords: digital media; social media; gender gap; online communication